Spatial and seasonal variation in reproductive indices of the clupeids Limnothrissa miodon and Stolothrissa tanganicae in the Congolese waters of northern Lake Tanganyika - N'sibula Mulimbwa T.; Milec Leona JM; Raeymaekers Joost AM; Sarvala Jouko; Plisnier Pierre-Denis; Marwa Beatrice; Micha Jean-Claude (ROYAL BELGIAN ZOOLOGICAL SOC, 2022)
Knowledge on the reproductive biology of the endemic clupeids Limnothrissa miodon and Stolothrissa tanganicae, two main target species of the pelagic fisheries of Lake Tanganyika, is constrained by fragmented monitoring activities. Here, we investigate the nursing areas of L. miodon, the timing of reproductive activities of littoral and pelagic L. miodon, and the timing of reproductive activities of pelagic S. tanganicae in the Congolese waters of the northern end of Lake Tanganyika (Bujumbura sub-basin). Nursing areas were determined year-round (2009-2010) based on the presence of clupeid larvae at two sandy and two stony beaches. The gonadosomatic index (GSI) and the proportion of fish having ripe gonads were used to study variation in reproductive indices in space (littoral vs. pelagic zones) during one year (2013-2014), as well as in time (dry vs. rainy season) during three years (2013-2016). Larvae of L. miodon were more frequently encountered on sandy than on stony beaches. Mature L. miodon females were more abundant in the littoral than in the pelagic zone, while the proportion of mature males in both habitats was similar. Irregular, low amplitude peaks could be distinguished in the GSI and proportion of mature males and females, but averages only differed between the dry and the rainy season in males. In contrast, GSI and proportions of mature males and females in S. tanganicae were higher in the dry season than in the rainy season. The reproductive effort of males and females of S. tanganicae and littoral L. miodon, but not pelagic L. miodon, was strongly synchronized. Interestingly, reproductive investment was also synchronised between pelagic male L. miodon, and pelagic S. tanganicae. Our time series strongly supports the view that L. miodon reproduces year-round in the littoral zone, while reproduction in S. tanganicae is seasonal. For fisheries management, we recommend year-round protection of sandy beaches, which are the main breeding grounds for L. miodon.